A bibliometric analysis of nursing research in COVID-19 in China - Ke PENG; Qiu-Lu MAI; Mei-Qi MENG; Dou WANG; Xiao-Yan ZHANG; Yu-Fang HAO (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this study is to analyze the current status of nursing research in COVID-19 through literature metrology and provide ideas and references for further research. Methods: The search terms such as "novel coronavirus/COVID-19" and "nursing" were used to search the nursing-related papers published in China National Knowledge Infrastructure, Wanfang Data, VIP Data, SinoMed, Web of Science, and PubMed from October 1, 2019, to March 30, 2020. The bibliometric methods and related software were used for analysis. Results: A total of 234 articles were included from 48 journals, and core journals accounted for 61.1%. There were five nursing literature topics and 14 document types. There is a cooperative relationship between six institutions. Keywords include nursing staff, nursing management, and protection. Conclusions: The opening of journal green channels and the establishment of database columns will help the spread of anti-epidemic academic results. The topics of nursing literature include clinical nursing, nursing management, prevention and control, nursing education, and social surveys. Nursing literature types focus on cross-sectional research and experience summary; the cooperation between researchers and research institutions has begun to take shape, and it is recommended to strengthen the research on iatrogenic injuries and nurse training in future nursing research.